Facile Synthesis of [1,2,3]-Triazole-Fused Isoindolines, Tetrahydroisoquinolines, Benzoazepines and Benzoazocines by Palladium-Copper Catalysed Heterocyclisation - Brahma, Kaushik; Achari, Basudeb; Chowdhury, Chinmay (Synthesis, 2013)
An elegant method for the synthesis of 1,2,3-triazoles fused with five-, six-, seven- and eight-membered benzoheterocycles, including isoindoline, tetrahydroisoquinoline, benzoazepine and benzoazocine, has been developed via palladium-copper catalysed reactions in one-pot. The broad scope of this reaction was illustrated by effecting bis-heteroannulations, synthesis of uracil derivatives of biological interest, and employment of acetylene gas as an inexpensive substrate. The reactions are experimentally simple and utilise easily accessible substrates of different types.
Keywords: 1,2,3-triazoles; nitrogen heterocycles; intramolecular reactions; azide-alkyne cycloaddition; bis-heteroannulations